(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
Selecting the most suitable manufacturing process for automotive bumper fascia is a complex decision-making problem due to the presence of multiple criteria and alternative options. This study presents a systematic evaluation to assess options by integrating the Analytic Hierarchy Process (AHP) and VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) methods. The objective is to determine the most appropriate manufacturing process for an automotive bumper fascia. Four potential manufacturing processes were evaluated, namely injection moulding, reaction injection moulding, compression moulding, and vacuum forming. The evaluation was based on six main selection criteria. AHP was used to determine the criteria weights, while VIKOR was applied to rank the alternatives. The integrated approach revealed that compression moulding (MP 3) is the most suitable manufacturing process for automotive bumper fascia. This combined decision-making framework effectively supports the selection of the optimal manufacturing process and can also be applied to other complex industrial decisions involving multiple factors.